Estrategias de enseñanza aplicadas a estudiantes con Dislexia en Básica Media en la Escuela de Educación Básica Municipal “Dr. Ángel Felicísimo Rojas” - Samaniego Songor., Mercy Dolores (2022)
The development of this research is of vital importance since it focuses on the approach of teaching strategies to counteract learning problems such as dyslexia. Being the main support tool for teachers to guide them and facilitate the understanding of reading and writing in students. The general objective of this study was to propose teaching strategies to improve the skills of students with Dyslexia in the Basic Media of the Municipal Basic Education School "Dr. Ángel Felicísimo Rojas” It also had three specific objectives: To describe teaching strategies aimed at reconstructing the reading and writing of students with dyslexia to improve their learning. To identify the strategies used by teachers to work with students with Dyslexia in the Basic Media School at the Municipal Basic Education School “Dr. Ángel Felicísimo Rojas”. And to design a guide with teaching strategies to improve literacy in students with Dyslexia in Basic Media at the Municipal Basic Education School “Dr. Angel Felicísimo Rojas. Likewise, in the present study, it has been carried out by applying the method documentary, hermeneutic, analytical, statistical, and techniques such as observation, the survey of teachers, obtaining information and expectations about teaching strategies to be applied to students with dyslexia; as well as instruments such as the questionnaire, the TEDE Test, enabling the measurement of dyslexia and later its statistical analysis, of the entire population of 50 basic media students. The descriptive statistics presented the results obtained, it was evidenced that there is dyslexia and it is at a low level. Keywords: strategy, dyslexia, teaching.